2008
DOI: 10.1002/art.23389
|View full text |Cite
|
Sign up to set email alerts
|

Association of interleukin‐23 receptor variants with ankylosing spondylitis

Abstract: Objective. Recent studies have shown that a nonsynonymous single-nucleotide polymorphism (SNP) (Arg381Gln; rs11209026) in the interleukin-23 receptor (IL-23R) gene on chromosome 1p31 is associated with Crohn's disease and psoriasis. Given the clinical and immunologic overlap between ankylosing spondylitis (AS) and these diseases, and the potential function of this candidate SNP, this study was undertaken to examine the association of IL-23R variants with AS in multiple Canadian populations.Methods. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(100 citation statements)
references
References 22 publications
5
89
0
6
Order By: Relevance
“…14 Subsequently, more studies have also associated this R/Q single nucleotide polymorphism with other diseases from different populations. 9,10,15,[17][18][19] Although investigating the IL23R for novel polymorphic elements, we discovered a range of novel splice variants of IL23R transcripts, greatly extending an earlier study by Zhang et al 20 from early 2006. We believe that understanding the role of these variants and how their presence is controlled will give us novel insight to the role of IL-23 in human Crohn's disease.…”
Section: Introductionsupporting
confidence: 59%
“…14 Subsequently, more studies have also associated this R/Q single nucleotide polymorphism with other diseases from different populations. 9,10,15,[17][18][19] Although investigating the IL23R for novel polymorphic elements, we discovered a range of novel splice variants of IL23R transcripts, greatly extending an earlier study by Zhang et al 20 from early 2006. We believe that understanding the role of these variants and how their presence is controlled will give us novel insight to the role of IL-23 in human Crohn's disease.…”
Section: Introductionsupporting
confidence: 59%
“…That suggested to the authors that IL-23R/STAT3 polymorphisms affecting T H 17 signaling efficiency were not major determinants for risk of Hashimoto's thyroiditis, at least in Croatians. Previous studies examining ankylosing spondylitis also indicated that the A allele frequency of R381Q was lower in spondylitis patients than in healthy controls (Rahman et al 2008;Duan et al 2012).…”
Section: Role For R381q Variant In Non-gastrointestinal Autoimmune DImentioning
confidence: 88%
“…, and CARD9 downstream of the dectin 1/Syk pathway, which transduces dendritic cell (DC) interleukin-23 (IL-23) secretion by fungal products, PTGER4, which encodes a prostaglandin receptor driving IL-23 secretion by DCs, and key signaling kinases and transcription factors associated with IL-23 receptor (IL-23R) signaling (3)(4)(5)(6)(7). IL-23 is required for the expansion and maintenance of T cells and innate immune cells secreting IL-17 and IL-22, and they are both implicated in the pathogenesis of SpA and Crohn's disease (8)(9)(10)(11).…”
Section: Il12bmentioning
confidence: 99%